2019
DOI: 10.1097/grf.0000000000000417
|View full text |Cite|
|
Sign up to set email alerts
|

Benzodiazepines in Pregnancy

Abstract: Benzodiazepine use and dependence are on the rise as well as the number of deaths attributable to the combination of opioids and benzodiazepines. Anxiety, the most frequent condition for which benzodiazepines are prescribed, occurs commonly, and is increasingly noted to coincide with pregnancy. Use of both benzodiazepine anxiolytics and anxiety in pregnancy is associated with preterm delivery and low birth weight. Short-term neonatal effects of hypotonia, depression, and withdrawal are described but long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 31 publications
0
25
0
3
Order By: Relevance
“…To avoid these hazards, people often use pharmacological and non-pharmacological treatments. It is well known that benzodiazepines and benzodiazepine-related drugs are generally prescribed for the treatment of anxiety disorders ( 43 ). These drugs have anxiolytic, hypnotic, and anticonvulsant properties and may relieve symptoms in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid these hazards, people often use pharmacological and non-pharmacological treatments. It is well known that benzodiazepines and benzodiazepine-related drugs are generally prescribed for the treatment of anxiety disorders ( 43 ). These drugs have anxiolytic, hypnotic, and anticonvulsant properties and may relieve symptoms in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…However, a causal relationship between etizolam and/or trazodone use during pregnancy and neonatal respiratory distress syndrome could not be ruled out. 9,10 To the best of our knowledge, this is the first report describing the transfer of etizolam across the placenta. Further studies are needed to evaluate potentially harmful effects following exposure to etizolam in utero and during breastfeeding.…”
mentioning
confidence: 87%
“…The effect of fetal exposure to benzodiazepins is largely unknown. In the general population, use of benzodiazepine for anxiety during pregnancy is associated with preterm delivery and low birth weight and potential short-term neonatal effects of hypotonia, depression, and withdrawal [70]. A methodologically sound study found no greater risk for lower language competence at ages 3 years [71].…”
Section: Benzodiazepinsmentioning
confidence: 98%
“…Concerning maternal epilepsy, there is an increased risk of neurodevelopmental disorders in pregnant women whose epilepsy is not optimally controlled, especially if the repeated seizures are generalized tonic-clonic [70].…”
Section: Other Factorsmentioning
confidence: 99%